Deleted mobile device's evidences recovery: a review international conference media & information warfare: a global challenge in the 21st century (M-i-war2007) / Yap Lee Fueng and Andy Jones - Yap, Lee Fueng; Jones, Andy (Centre for Media and Information Warfare Studies, 2008)
This paper presents the finding and results obtaineq from using commercial forensic investigation software tools to recover deleted evidences from mobile device's S/M cards, internal and external memories. The results obtained from the investigation are classified and discussed and finally, the paper highlights the limitation of the software based techniques deployed for deleted evidences recovery and presents conclusions.